Ablood flow-dependent klf2a-NO signaling cascade is required for stabilization of hematopoietic stem cell programming in zebrafish embryos - Wang, L; Zhang, P; Wei, Y; Gao, Y; Patient, R; Liu, F (2011)
Blood flow has long been thought to be important for vessel development and function, but its role in HSC development is not yet fully understood. Here, we take advantage of zebrafish embryos with circulation defects that retain relatively normal early development to illustrate the combinatorial roles of genetic and hemodynamic forces in HSC development. We show that blood flow is not required for initiation of HSC gene expression, but instead is indispensable for its maintenance. Knockdown of klf2a mimics the silent heart (sih/tnnt2a) phenotype while overexpression of klf2a in tnnt2a morphant embryos can rescue HSC defects, suggesting that klf2a is a downstream mediator of blood flow. Furthermore, the expression of NO synthase (nos) was reduced in klf2a knockdown embryos, and ChIP analysis showed that endogenous Klf2a is bound to the promoters of nos genes in vivo, indicating direct gene regulation. Finally, administration of the NO agonist S-nitroso N-acetylpenicillamine (SNAP) can restore HSC development in tnnt2a and klf2a morphants, suggesting that NO signaling is downstream of Klf2a which is induced by hemodynamic forces. Taken together, we have demonstrated that blood flow is5 essential for HSC development and is mediated by a klf2a-NO signaling cascade in zebrafish. © 2011 by The American Society of Hematology.